2018
DOI: 10.1083/jcb.201711065
|View full text |Cite
|
Sign up to set email alerts
|

SAC-1 ensures epithelial endocytic recycling by restricting ARF-6 activity

Abstract: Arf6/ARF-6 is a crucial regulator of the endosomal PI(4,5)P2 pool in endocytic recycling. Chen et al. show that SAC-1 is important for epithelial cell recycling in C. elegans. SAC-1 acts as a novel interactor for ARF-6, curbing ARF-6 activity by limiting the access of ARF-6(GDP) to its GEF BRIS-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 101 publications
(191 reference statements)
2
13
0
Order By: Relevance
“…Through confocal stack imaging of intestinal epithelial cells from intact living animals ( Fig 1B), we found that, in both sid-3 mutants, the number and size of hTAC-GFP-labeled intracellular structures increased significantly (~9-fold increase in total area) ( Fig 1C-1C''). This phenotype is typical of basolateral recycling mutants [5,12,[28][29][30]. We further assayed the accumulation of FGT-1, the worm homolog of another clathrin-independent recycling cargo, GLUT1 [8], and observed that SID-3 deficiency led to substantial intracellular aggregation of FGT-1-positive structures (~7.8-fold increase in total area) (S1A and S1A ' Fig).…”
Section: Loss Of Sid-3 Causes Endocytic Recycling Defectsmentioning
confidence: 82%
“…Through confocal stack imaging of intestinal epithelial cells from intact living animals ( Fig 1B), we found that, in both sid-3 mutants, the number and size of hTAC-GFP-labeled intracellular structures increased significantly (~9-fold increase in total area) ( Fig 1C-1C''). This phenotype is typical of basolateral recycling mutants [5,12,[28][29][30]. We further assayed the accumulation of FGT-1, the worm homolog of another clathrin-independent recycling cargo, GLUT1 [8], and observed that SID-3 deficiency led to substantial intracellular aggregation of FGT-1-positive structures (~7.8-fold increase in total area) (S1A and S1A ' Fig).…”
Section: Loss Of Sid-3 Causes Endocytic Recycling Defectsmentioning
confidence: 82%
“…Previous studies reported that CD147 is internalized through Rab5-associated CIE, recycled via Rab22-dependent endosomes, and by-passed merging with the EEA1-positive endosomes in cervical cancer cells [1315]. Arf6 (ADP-ribosylation factor 6) is another GTPase that regulates the endocytic recycling process in concert with different Rab GTPases [2, 1622]. Arf6 activation can further promote CD147 trafficking, especially to accelerate it entering in the fast recycling pathway [15, 23].…”
Section: Introductionmentioning
confidence: 99%
“…, 2016 ). Intriguingly, in Caenorhabditis elegans, Sac1 inhibits Arf6 by sequestering the Arf6-GEF Bris-1 ( Chen et al. , 2018 ).…”
Section: Discussionmentioning
confidence: 99%